Effect of remote vs. face-to-face feedback on the manual dexterity acquisition process in a haptic virtual reality simulator: a pilot study - Lévano Loayza, Sandro Alexander (2023)
Haptic Virtual Reality (HVR) simulators are increasingly crucial in modern clinical education. Within this context, the significance of feedback provided by instructors to students is evident. This feedback can be delivered either face-to-face or remotely, the latter facilitated by an individualized audio and microphone system. However, there is limited literature exploring and illustrating the advantages and disadvantages of these two approaches. Objective: To determine the impact of remote vs. face-to-face feedback on the process of acquiring manual dexterity using an HVR simulator among first-year students at the School of Stomatology of Universidad Peruana Cayetano Heredia. Material and methods: A study was conducted involving 37 participants (mean age = 18.2 years; SD = 3.2 years) without prior dental training. They were randomly assigned to three groups (n1 = 17; n2 = 10; n3 = 10). Group 1 received only face-to-face feedback; Group 2 received exclusively remote feedback; and Group 3 received no feedback. All three groups were required to complete the same exercise within the same designated time frame. Results: Significant differences were observed among groups in overall performance, encompassing both unsuccessful and successful attempts. However, there was no distinction in terms of the time taken or the number of attempts made during practice. Conclusions: The acquisition of manual dexterity among novice dental students through basic exercises is optimized by utilizing remote feedback in conjunction with an HVR simulator.